THE RELATIONSHIP OF LEARNING HABITS WITH STUDENTS' COGNITIVE AREA LEARNING OUTCOMES IN CLASS IV PPKN SDN 03 SINGKAWANG - Alvera Alvera; Rien Anitra; Evinna Cinda Hendriana (PROGRES PENDIDIKAN, 2022)
This study aims to: 1) describe the study habits of fourth grade students at SDN 03 Singkawang; 2) Describe the cognitive domain learning outcomes of fourth grade students at SDN 03 Singkawang; 3) determine the relationship between study habits and learning outcomes of fourth grade students at SDN 03 Singkawang. The research method is correlational or relationship with a quantitative approach. The sample of this study was students of class IV A and IV B at SDN 03 Singkawang with 24 students for class IV A. The technique used was the purposive sampling technique. The 5% (0.05) significant level data used was the normality test using the Chi square formula. The results showed; 1) study habits in the medium category as many as 24 students with a percentage of 69%; 2) Learning outcomes in the cognitive domain with a good category were 11 students with a percentage of 70%; 3) There is a relationship between study habits and learning outcomes in the cognitive domain with the criteria for the strength of the relationship in the fairly strong category with a correlation coefficient of 0.40. Learning habits provide a determinant coefficient of 16% of learning outcomes in the cognitive domain and the difference of 84% is influenced by other factors. Thus, it can be concluded that if students' learning habits are high, the higher the cognitive domain learning outcomes. On the other hand, the lower the student's study habits, the lower the student's cognitive domain learning outcomes.